Leveraging informal learning practices for broadening participation in university education: A Kenyan case study - Roxanne Hawi; Eva Heinrich; Sunil Lal (Journal of Open, Flexible and Distance Learning, 2021)
Kenyan public universities primarily provide classroom-based courses. However, socioeconomic realities limit many rural-based learners from regularly attending classes. Interestingly, because of the willingness of Kenyans to further their education, informal education is picking up fast. Individuals are forming informal learning circles and have proactively found ways to use smartphones to access online educational resources. This paper explores ways to leverage the strengths of these informal learning practices to enhance participation in formal higher education for Kenyans. One way this can be achieved is through blended learning. With blended learning, students will experience the convenience of online learning without losing the social on-campus interactions they are accustomed to. Currently, the use of blended learning in Kenyan public universities is not at the desired level. Lack of conventional computing resources (laptops/desktop PCs) due to economical constraints is a contributing factor. Given their widespread adoption, we suggest smartphones could serve as a viable platform for blended learning in Kenya. To explore this idea, a survey was conducted with 114 students in Tom Mboya University College (TMUC), a rural-based public university in Kenya. The survey examined students’ attitudes towards using smartphones in education. Results indicate smartphones are already an integral part of the students’ informal education and the students have a strong desire to integrate smartphones into their formal education. We envisage that our research will contribute knowledge towards the adoption of blended learning in resource-constrained university environments.